Translocation of Endogenous Danger Signal HMGB1 From Nucleus to Membrane Microvesicles in Macrophages. Issue 11 (9th March 2016) - Chen, Yan; Li, Guangping; Liu, Yanxia; Werth, Victoria P.; Williams, Kevin Jon; Liu, Ming‐Lin
Abstract : High mobility group box 1 (HMGB1) is a nuclear protein that can be released from activated or dead cells. Extracellular HMGB1 can serve as a "danger signal" and novel cytokine that mediates sterile inflammation. In addition to its soluble form, extracellular HMGB1 can also be carried by membrane microvesicles. However, the cellular mechanisms responsible for nuclear HMGB1 translocation to the plasma membrane and release onto membrane microvesicles have not been investigated. Tobacco smoking is a major cause of sterile inflammation in many diseases. Smoking also increases blood levels of HMGB1. In this study, we found that exposure of macrophages to tobacco smoke extract (TSE) stimulated HMGB1 expression, redistribution, and release into the extracellular milieu both as a soluble molecule and, surprisingly, as a microvesicle‐associated form (TSE‐MV). Inhibition of chromosome region maintenance‐1 (CRM1), a nuclear exporter, attenuated TSE‐induced HMGB1 redistribution from the nucleus to the cytoplasm, and then its release on TSE‐MVs. Our study demonstrates a novel mechanism for the translocation of nuclear HMGB1 to the plasma membrane, and then its release in a microvesicle‐associated form. J. Cell. Physiol. 231: 2319–2326, 2016. © 2016 Wiley Periodicals, Inc.